PENGARUH KINERJA KEUANGAN DAN DEWAN KOMISARIS TERHADAP FINANCIAL DISTRESS - Melati Napitupulu, Ravlecia; Suryandari, Dhini (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The purpose of this study aims to determine the influence of WCTA, RETA, EBITTA, BVE / BVL and the board of commissioners on the possibility of financial distress in the company. The data analysis method uses descriptive statistical analysis and logistic regression analysis using the IBM SPSS Version 21 application. The population of this study is a coal mining sector company listed on the Indonesia Stock Exchange (IDX) in 2017-2020 which amounted to 26 companies. From 26 companies obtained a sample of 18 coal mining companies with 72 units of analysis. The sampling technique in this study used purposive sampling. The data is an annual report and financial statements published by companies registered with the IDX. The results of this study showed that WCTA, BVE/BVL, EBITTA had a negative and significant effect on financial distress. RETA had a positif and significant effect on financial distress and board of commissioners had no significant effect on financial distress. The conclusion of this study is WCTA, RETA, EBITTA has a negative and significant effect on financial distress, while BVE / BVL and the board of commissioners have no significant effect on financial distress. Keywords: Financial Distress, Financial Performance, Board of Commissioners, Springate Model